Research on mechanics of ship-launching airbags I—Material constitutive relations by numerical and experimental approaches. (August 2015) - Yu, Long; Li, Yao; Xia, Lijuan; Ding, Jinhong; Yang, Qi
Highlights: A theoretical and an FE constitutive model for sandwiched membrane of airbags. Uniaxial tensile tests and their numerical simulations with good agreements. Isotropic and orthotropic material models were developed and compared. Model-scale loaded airbags computed theoretically and by FE analysis for validation. Abstract: Ship-launching airbags are widely used in small- and medium-scale Chinese shipyards as a cost-effective substitute for slipways; they are capable of handling launching ship with weights of up to 70, 000 tons. However, throughout the 30-year history of these airbags, the safety of the launching process has depended on the high bearing capacity of the airbags and the operators' experience. Very little theoretical research has been conducted on the ship-launching airbags, and no material constitutive model has yet been established for a ship-launching airbag, especially one that addresses the sandwiched hyperelastic membrane. This study, therefore established a constitutive model for an airbag membrane with reinforcement, through both uniaxial tensile tests and numerical simulations. Isotropic and orthotropic models were developed and compared. The obtained results were found to be in good agreement with the actual test data. Another different size tensile test has also been carried out for eliminating uncertainty of the test. Finally, model-scale data for loaded ship-launching airbags were modeled and computed both theoretically and by Finite Element analysis. The stress and strain results were compared with pressing test data to demonstrate the applicability of the constitutive model to the prediction of safety of using airbags for launching a ship.